Gute Gesinnung oder prüfende Forschung? Eine Erwiderung zu Jürgen Mansels Replik - Reichertz, Jo (1994)
This article is a response to Jürgen Mansel's critical review of Reichertz' and Schoer's contribution to the previous issue of this journal. The authors reply that a) in the present case the use of qualitative research techniques is not only practicable but also the most adequate method to be used in this problem area and b) that their explaining hypotheses are orientated by a sociology of culture approach. They reproach Jürgen Mansel an inclination for a sentimental and not a value free sociological disposition.